Alterations in the gut microbiota and metabolite profiles of thyroid carcinoma patients. Issue 11 (24th December 2018) - Feng, Jing; Zhao, Fuya; Sun, Jiayu; Lin, Baiqiang; Zhao, Lei; Liu, Yang; Jin, Ye; Li, Shengda; Li, Aidong; Wei, Yunwei
Abstract : The aim of our study was to investigate the relationship among the gut microbiota community, metabolite profiles and thyroid carcinoma (TC). First, 30 TC patients and 35 healthy controls (HCs) fecal samples were applied to characterize the gut microbial community using 16S rRNA gene sequencing. Differential microbiota compositions were observed, with significant enrichment of 19 and depletion of 8 genera in TC samples compared to those in HCs ( Q value <0.05), and some genera were correlated with various clinical parameters, such as lipoprotein A and apolipoprotein B. Furthermore, 6 different genera distinguished TC patients from HCs with the AUC of 0.94. The PICRUSt analysis showed 12 remarkably different metabolic pathways ( Q value <0.05). Subsequently, we systematically analyzed the gut microbiota and metabolites in the same TC patients ( n = 15) and HCs ( n = 15). The characteristics of the gut microbiota community were mostly consistent with the above results (30 TC patients and 35 HCs), and liquid chromatography mass spectrometry analysis was performed to characterize the metabolite profiles. In total, 21 different genera ( Q value <0.05) and 72 significantly changed metabolites (VIP > 1.0 and p < 0.05) were observed and correlated to each other. Eight metabolites combined with 5 genera were more effective in distinguishing TC patients from HCs (AUC = 0.97). In conclusion, our study presents a comprehensive landscape of the gut microbiota and metabolites in TC patients, and provides a research direction of the mechanism of interaction between gut microbiota alteration and TC pathogenesis. Abstract : What's new? Evidence suggests that gut microbiota and metabolites modulate and potentially control carcinoma initiation and progression. Here, the authors investigated associations between gut microbiota, fecal metabolite profiles, and thyroid carcinoma. Gut microbial communities from patients with thyroid carcinoma and from healthy controls were found to differ significantly, with enrichment and depletion of multiple microbial genera in thyroid carcinoma. Differences were also identified in fecal metabolite composition, with 72 metabolites showing significant changes. Thyroid carcinoma patients were successfully identified from a combination of eight metabolites and five genera. The findings further implicate alterations in gut microbiota and metabolites in thyroid carcinoma development.